2003
DOI: 10.1002/anie.200352232
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Transfer from Single Molecules into Self‐Assembled Monolayers

Abstract: Chemie CommunicationsChirality transfer from single molecules into handed supramolecular structures is studied by self-assembly of chiral molecules on solid surfaces. Each "mountain" in the STM image represents a single M heptahelicene molecule on a Cu(111) surface. The P enantiomer forms the mirror-image structure. For more information see the following Communication by Fasel, Ernst, and Parschau.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
179
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(189 citation statements)
references
References 37 publications
9
179
0
1
Order By: Relevance
“…20b and c. The Menantiomer shows the corresponding mirror structures, i.e., with opposite handedness (not shown) [122]. XPD revealed that three rings on the proximal end are aligned parallel to the surface plane [35], and force-field calculations for the saturation structure provided a model in good agreement with the observations (Fig.…”
Section: Racemic Mixturessupporting
confidence: 60%
See 1 more Smart Citation
“…20b and c. The Menantiomer shows the corresponding mirror structures, i.e., with opposite handedness (not shown) [122]. XPD revealed that three rings on the proximal end are aligned parallel to the surface plane [35], and force-field calculations for the saturation structure provided a model in good agreement with the observations (Fig.…”
Section: Racemic Mixturessupporting
confidence: 60%
“…A formation of the enantiomorphous (4-1, 2 4) phase is not observed for the racemic mixture, which saturates in a c(2 Â 4) structure [119]. Other than tartaric acid, racemic heptahelicene ( [7]H; C 30 H 18 ) forms completely different structures from the pure enantiomers on Cu(111) [122][123][124][125]. This aromatic hydrocarbon is basically a construct of seven orthoannulated C6 rings and therefore an example of a chiral molecule without a stereogenic center (Fig.…”
Section: Racemic Mixturesmentioning
confidence: 99%
“…54−56 In that case, the chirality of the molecule is transferred to the molecular assembly. 57 Chiral structure can also be achieved using achiral molecules. 1,54,55,58,59 In that case, the chirality results from the specific arrangement of the molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1c. [10] Similar to the frustrated lattice structures observed for crystalline polymers of single helicity, e.g . isotactic poly(propylene), [12] not all helices can be aligned 'in phase'.…”
Section: Transfer Of Handedness From Single Molecules Into 2d Crystalsmentioning
confidence: 55%
“…One example are the pure [7]H enantiomers on Cu(111). [10] Close to monolayer saturation, handed pinwheel structures are observed via STM (Fig 1a,b). The ( M )- [7]H-pinwheels have the opposite handedness to the ( P )- [7] H-pinwheels.…”
Section: Transfer Of Handedness From Single Molecules Into 2d Crystalsmentioning
confidence: 87%